2018
DOI: 10.18268/bsgm2018v70n2a1
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Early Jurassic arthropod trackways Camurichnus and Hamipes

Abstract: RESUMEN Los icnogéneros Camurichnus y Hamipes ABSTRACTThe ichnogenera Camurichnus and Hamipes have been reevaluated based on examination of their type specimens, and their geographic and stratigraphic ranges determined based on a review of the literature. The characteristics used to distinguish Camurichnus (originally erected as Sagittarius) and its included ichnospecies alternans, have been observed in Bifurculapes laqueatus and therefore Camurichnus alternans is considered a junior subjective synonym of B. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Second, Bolliger & Gubler (1997) hypothesized that their novel, early Miocene ichnospecies Hamipes molassicus was made by a buoyed (presumably swimming) crayfish. Getty (2018) referred these specimens to Conopsoides ; later, Getty & Burnett (2019) suggested that at least some of the specimens may pertain to Acanthichnus , and they differ from SGDS 1290 for the same reasons outlined above for Acanthichnus . Third, De Gibert et al (2000) attributed Early Cretaceous, Spanish specimens that they assigned to Hamipes didactylus to crayfish.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, Bolliger & Gubler (1997) hypothesized that their novel, early Miocene ichnospecies Hamipes molassicus was made by a buoyed (presumably swimming) crayfish. Getty (2018) referred these specimens to Conopsoides ; later, Getty & Burnett (2019) suggested that at least some of the specimens may pertain to Acanthichnus , and they differ from SGDS 1290 for the same reasons outlined above for Acanthichnus . Third, De Gibert et al (2000) attributed Early Cretaceous, Spanish specimens that they assigned to Hamipes didactylus to crayfish.…”
Section: Discussionmentioning
confidence: 99%
“…Third, De Gibert et al (2000) attributed Early Cretaceous, Spanish specimens that they assigned to Hamipes didactylus to crayfish. Getty (2018) attributed these tracks to Bifurculapes and maintained a crustacean track maker for H. didactylus , but was not more specific. However, neither Bifurculapes nor Hamipes resemble experimentally generated crayfish traces ( Fairchild & Hasiotis, 2011 ), or any of the mortichnial decapod traces, and thus are unlikely to have been made by a crayfish-like decapod, at least while walking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations